Penilaian Adaptasi dan Strategi Mitigasi Perubahan Iklim pada Masyarakat Agraris di Kordofan Utara Sudan - Mohammed Mohammed; Salih Omer Tutu; Hassan Elnour Adam; Alawia Osman Koli; Abdalla Nourain Omer Abdalla (Fakultas Kehutanan Universitas Gadjah Mada, 2021)
The current study was conducted in Bara Locality- North Kordofan - Sudan to assess climate change adaptation and mitigation strategies among agrarian communities. Qualitative and quantitative data were collected by randomly interviewing 150 respondents from ten villages, using questionnaire. Descriptive statistics in SPSS software package and Microsoft Excel were used for data analysis. Results of study showed that agrarian communities, and due to climate change, have enforced to develop ten adaptation strategies suitable for agriculture in dryland conditions. The most adaptation strategies being used by the agrarian communities, are cultivation in different directions locally Sheraik (77%), sowing before rain locally Ramail (77%) and reducing cultivated area as mentioned by 67% of interviewed respondents. In forests sector, around 65 % of the interviewed respondents have been practiced agro-forestry as an adaptation strategy. The interviewees were also able to figure out 6 possible mitigation strategies to stave off climate change effects. These strategies are for example building capacity of agrarian communities (73%) and provision of early mature, high yielding and drought tolerant crops (63%). The study come out with some suggestions in order to pave the way for policymakers to tailor suitable future interventions to mitigate the impact of climate change among agrarian communities.